Consumer confidence index in the city of Riobamba - Álvarez Basantes, Karina; Cortez Viteri, Ayrton; González Bautista, María; Zurita Moreano, Eduardo (mktDESCUBRE; Vol 1 No 19 (2022): Nineteenth Edition (January - June)DO - 10.36779/mktdescubre.v1i19.679, 2022)
The Consumer Confidence Index (CCI) shows the level of optimism that households have regarding current perceptions and consumption expectations, the household's economic situation and the country's economic scenario; becoming a key indicator of the general state of the economy. For the calculation of the ICC, the methodology established by the Central Bank of Ecuador (BCE) was used, 382 surveys were applied in the urban area of ​​the city of Riobamba, with qualitative questions. The importance assigned to each of the answers is categorized into three levels: worst, equal or better, with weights of 0, 50 and 100 points, respectively. In this way, the total value of the ICC ranges between 0 and 100 points, where values ​​below 50 and close to 0 represent a pessimistic scenario, while a value above 50 or close to 100 represents a positive scenario. An ICC of 46.51 points was obtained, which shows that there is still no consumer confidence when purchasing goods or services, this is mainly due to the fact that the country's economy has been hit hard, the main cause is the coronavirus pandemic. SARS-COVID 19 virus.